Mementos of a love faraway - Gostič, Maja (Dve domovini, 2023)
This article explores the role of everyday objects in long-distance relationships (LDRs) that connect two geographically distant partners. Focusing on LDRs within Europe, the study is based on interviews with people in such relationships. The article discusses one of the practices of creating a partner’s abstract presence, called recognizing the sentimental value of objects. As part of developing and maintaining intimacy in the relationship, imagining the partner’s presence is reinforced through emotional objects. The article contributes to the intersection of material culture and mobility studies by exploring the role of objects in emotionally linking geographically distant partners.
Keywords: abstract presence; abstraktna prisotnost; čustveni predmeti; emigrants; emotional objects; intimacy; intimnost; izseljenci; ljubezen; long-distance relationships; love; subjective experiences; zveze na daljavo